2019
DOI: 10.1101/546374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restoration of Direct Corticospinal Communication Across Sites of Spinal Injury

Abstract: Injury to the spinal cord often disrupts long-distance axon tracts that link the brain and spinal cord, causing permanent disability. Axon regeneration is then prevented by a combination of inhibitory signals that emerge at the injury site and by a low capacity for regeneration within injured neurons. The corticospinal tract (CST) is essential for fine motor control but has proven refractory to many attempted pro-regenerative treatments. Although strategies are emerging to create relay or detour circuits that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Next, we tested whether corticospinal reorganization promotes recovery of forelimb function after cervical SCI. We first confirmed that corticospinal function is required during forelimb skilled walking (4). To test this, we injected AAV particles expressing the designer receptor exclusively activated by designer drug (DREADD) hM4Di (27) into the right sensory-motor cortex to transiently silence the corticospinal pathway on 1 side of adult naive mice when clozapine N-oxide (CNO) is administered (Supplemental Figure 7A).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Next, we tested whether corticospinal reorganization promotes recovery of forelimb function after cervical SCI. We first confirmed that corticospinal function is required during forelimb skilled walking (4). To test this, we injected AAV particles expressing the designer receptor exclusively activated by designer drug (DREADD) hM4Di (27) into the right sensory-motor cortex to transiently silence the corticospinal pathway on 1 side of adult naive mice when clozapine N-oxide (CNO) is administered (Supplemental Figure 7A).…”
Section: Resultsmentioning
confidence: 90%
“…Recovery of spinal cord function in adults might be attained by promoting axon sprouting, regeneration, and de novo formation of neural circuits (2)(3)(4). Among the descending pathways important for SCI repair, the corticospinal tract exerts the sensory and motor control that is necessary for accurate limb placement and voluntary movements (5).…”
Section: Introductionmentioning
confidence: 99%
“…AAV6 [48] and a directed evolved variant of AAV2 named 'AAV2-Retro' [49] have the capability for retrograde transduction in the CNS. AAV2-retro has been applied for robust transduction of the CST by injection into the spinal cord of adult mice [50,51].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…While these barriers to remyelination and regeneration have been a source of consternation for scientists and clinicians alike, technological advances in the last decade have greatly improved prospects. One preprint from the Blackmore lab utilizing cell transplantation paired with pro-regenerative gene delivery and growth permissive grafting showed enhanced axon regeneration and functional recovery in a murine SCI model (Jayaprakash et al, 2019 ). Such combination therapies hold considerable promise in the treatment of TBI/SCI.…”
Section: Demyelination Following Traumatic Injurymentioning
confidence: 99%
“…While there is strong therapeutic potential for CRT itself, combinatorial approaches continue to yield the best results in TBI/SCI. Cell transplantation has been paired with RNAi, electrical stimulation, as well as a variety of small molecules to promote neurophysiological recovery (Karimi-Abdolrezaee et al, 2006 ; Zhang et al, 2012 ; Jayaprakash et al, 2019 ). The use of combination therapies has been especially beneficial in developing treatments for chronic SCI.…”
Section: Translational Approaches In Animal Modelsmentioning
confidence: 99%